Papaya flowering as a subsidy for the plant breeding of the crop – literature review (Research, Society and Development, 2022)
The productive success of papaya is the result of several factors that are intrinsic to the cultivar, management and environmental conditions during its vegetative and reproductive cycle. After starting flowering and, consequently, production, the papaya tree continues the reproductive process throughout its life cycle. However, during the course of this cycle, climatic instabilities may result in disturbances in flowering and fruit development, affecting crop yield. The date of occurrence of the phases such as sprouting, flowering, fruiting, fruit maturation and leaf fall and the duration of the sub-periods are related to the intensity of the meteorological elements. Thus, phenological studies are fundamental, as they allow better planning for hybridization, aiming at obtaining hybrid seeds for the cultivar development program, in addition to generating information on the development of the culture in relation to the environment, especially to climatic variations. seasonal. In this one, a bibliographic review was carried out on the theme of flowering in the papaya crop. In this way, topics were addressed regarding concepts, floral anomalies, study of sexual inheritance in papaya and varieties used, using articles from 2010 to 2021. Climatic factors are among the limiting factors for papaya production, as they influence growth and flowering, consequently reflecting on fruit production. Knowledge of the behavior of cultivated species in relation to the phenological cycle, such as maturation uniformity, cycle duration and flowering, is essential to support research aimed at genetic improvement.